Comparative study of bacterial microfiltration in the implant‐abutment interface, with straight and conical internal connections, in vitro - Larrucea V. Carlos; Navarro C.Carlos; Larrucea SM.Karina; Boda K.Sunil; Padilla E.Carlos; Lobos G.Olga (Wiley, 2021)
Abstract Objective to determine the presence of marginal bacterial microfiltration in the IAI in different implant/abutment systems, in vitro. Material and methods Fifty‐six implants from seven different brand names, 4 with cone and 3 with straight connections were used, implant and abutment were connected using the Ncm tightening as indicated by each of the manufacturers and then were sealed. The samples were subjected occlusal load and thermal cycling, a first sample of each group was observed by micro CT and in a second sample (both samples randomly selected) length of connection was measured, while the rest of the samples were mounted on devices according to the bacterial microfiltration model with Porphyromonas gingivalis. Results Two of the conical connection system groups did not present bacterial microfiltration, one of the three straight connection groups only microfiltered in one sample, while the other two conical as well as the two straight connection samples showed different and important levels of bacterial microfiltration, all groups presented a direct relationship between the implant‐abutment adjustment determined by micro‐CT and bacterial microfiltration levels, not related to the connection length. Conclusion: Only two conical connection systems presented no bacterial microfiltration.